Aspectos sociais do Matopiba: Análise sobre o desenvolvimento humano e a vulnerabilidade social - Gabriela Lanza Porcionato; César Nunes de Castro; Caroline Nascimento Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The word Matopiba refers to the region that is formed by municipalities in the frontier of the states of Maranh\~ao, Tocantins, Piauí and Bahia, which in the last two decades has been rapid transformations in its dynamics of land occupation due to expansion of the agricultural activity, a production of grains, mainly of soybean. Although studies show the accelerated expansion of soy, on the other hand, studies show that the disparities resulting from the prosperity of production, such as the concentration of income. Thus, the goal of this article is to provide information on social issues for Matopiba region. This article has information in municipal terms, about living conditions of the resident population in the region. According to data, an improvement of the Municipal Human Development Index (HDI) and Social Vulnerability Index (IVS) in the region as a whole to improve the social conditions and economic dynamism of the region. While the improvement, highlighting that the Matopiba region still presents low and medium Municipal Human Development Index (HDI) in most municipalities, and low and medium Social Vulnerability Index (IVS). Therefore, while the prominence in the production and commercialization of soybeans in the agribusiness sector, the region presents persistence with regard to expressive regional inequality if we compare with the rest of the country.
Keywords: R1; R10; 330; Matopiba; social aspects; human development; social vulnerability